2007
DOI: 10.1093/gerona/62.7.744
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and Risk of Falls, Fracture, and Mortality in Older Women: The Study of Osteoporotic Fractures

Abstract: Background. A standard phenotype of frailty was associated with an increased risk of adverse outcomes including mortality in a recent study of older adults. However, the predictive validity of this phenotype for fracture outcomes and across risk subgroups is uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
474
7
20

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 631 publications
(533 citation statements)
references
References 35 publications
32
474
7
20
Order By: Relevance
“…These findings can be grouped in the phenotype of frailty syndrome. Although this syndrome has no well-defined classification criteria, a number of authors state that the presence of three or more items (unintentional weight loss, weakness, self-reported reduction in energy, low degree of physical activity and slower gait) can be used to identify frail patients, regardless of age, weight or gender 32,33,34 . In the present study, we applied clinical frailty criteria based on self-reported data from individuals aged 65 and older, but there was only a tendency toward an association to a greater risk of recurrent falls (p = 0.06).…”
Section: Discussionmentioning
confidence: 99%
“…These findings can be grouped in the phenotype of frailty syndrome. Although this syndrome has no well-defined classification criteria, a number of authors state that the presence of three or more items (unintentional weight loss, weakness, self-reported reduction in energy, low degree of physical activity and slower gait) can be used to identify frail patients, regardless of age, weight or gender 32,33,34 . In the present study, we applied clinical frailty criteria based on self-reported data from individuals aged 65 and older, but there was only a tendency toward an association to a greater risk of recurrent falls (p = 0.06).…”
Section: Discussionmentioning
confidence: 99%
“…[30][31] Similarly, the fear of falling by the elderly (psychological trauma, evidenced especially after an episode of fall with serious injuries) may be a result of frailty. Fear of falling can lead the elderly to take cautious behaviors that aid in fall prevention, but in contrast, these behaviors may reduce trust and participation in activities, favoring the functional decline (selfprotective immobility), and thus, increase the risk of frailty or its worsening.…”
Section: Consequences Of Frailty In the Elderlymentioning
confidence: 99%
“…The fear of falling influence changes on the temporal-spatial parameters in the elderly, leading to a slower march (in this case, it is decisive). 30 The reduction of march speed, which is a frailty attribute, is a major risk of falls and, in this case, the fear of falling becomes a consequence. In this study, although these events are judged as frailty consequences, it is considered the aspects already mentioned.…”
mentioning
confidence: 99%
“…1 Devido a sua repercussão na saúde dos idosos, a queda é considerada um evento limite, pois em geral está associada a fragilidade, dependência, institucionalização e morte. 2 Sendo assim, as quedas são consideradas um problema de saúde pública, já que sua ocorrência está relacionada a altas taxas de morbimortalidade, além do elevado custo social e econômico. 3 Nos Estados Unidos, acidentes e lesões não intencionais ocupam o quinto lugar entre as causas de morte na população idosa, sendo as quedas responsáveis por dois terços destas.…”
Section: Introductionunclassified